Lonestar Homecoming - Coble, Colleen (Nashville, Tenn. : Thomas Nelson, 2009)
"With nothing but five dollars and the wedding dress she's wearing, Gracie Lister flees with her daughter by train to West Texas..."--p. [4] of cover.
Keywords: Single mothers -- Fiction; Man-woman relationships -- Fiction; Texas -- Fiction; Romantic suspense fiction; Christian fiction, American; Love stories